Psychometric Properties of the Reactive-Proactive Aggression Questionnaire Among a Sample of Detained and Community Girls - Pechorro, Pedro (Criminal justice and behavior, 2017)
Research on adolescent aggression often distinguishes between reactive and proactive aggression, but there is limited knowledge regarding the application or measurement of these subtypes of aggression among female youth, especially forensic samples of female youth. Drawing on 377 girls (103 selected from forensic settings and 274 selected from school settings) from Portugal, the current study is the first to simultaneously examine the psychometric properties of the Reactive-Proactive Aggression Questionnaire (RPQ) in incarcerated girls and community girls. The results support the use of the RPQ in terms of its two-factor structure, measurement invariance, internal consistency, convergent validity, discriminant validity, and known-groups validity. Significant associations were found with several criterion-related variables such as age of criminal onset, age of first problem with the law, conduct disorder, crime severity, violent crimes, and alcohol and drug use. Findings are discussed in terms of the use of the RPQ among incarcerated girls and community girls.